The Effect of Progressive Muscle Relaxation Therapy on Sleep Quality in Elderly Hypertensive Patients - Irawan, Erna; Iklima, Nurul; Maidartati, M; Ningrum, Tita Puspita; Safira, Yulia (Journal Medical Informatics Technology, 2024)
Hypertension causes sleep quality disturbances. A cost-effective and accessible intervention for sleep quality issues is progressive muscle relaxation therapy, a non-pharmacological approach that can improve sleep quality by alleviating negative feelings and promoting comfort and relaxation in the muscles. The objective of this study was to determine the effect of progressive muscle relaxation therapy on the sleep quality of elderly hypertensive patients at UPT Puskesmas Babakan Sari RW 14, Bandung City.   This study employed a quasi-experimental design with a one-group pre-post test. The population consisted of 118 hypertensive patients, and accidental sampling was used, resulting in 15 respondents visited at their homes. The sleep quality was measured using the PSQI questionnaire. Data analysis included univariate analysis using frequency distribution and bivariate analysis using the paired samples T-Test.  Results showed that the average PSQI score before the intervention was 9.93, which decreased to 4.0 after the intervention. The paired samples T-Test with T value of 6.615 (df=34) and a correlation of 0.770 and a significance level of 0.000 (P<0.05), indicating a significant effect of progressive muscle relaxation on sleep quality.   There is an effect of progressive muscle relaxation therapy on the sleep quality. Hypertensive patients are encouraged to continue practicing progressive muscle relaxation weekly to improve sleep quality and help control blood pressure.